Occurrence of scabies among the outpatient children of Dhaka Medical College, Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2010)
A cross-sectional type of study was carried out among children under 12 years attending the department of skin and venereal diseases (VD) of Dhaka Medical College Hospital, with the objective of investigation about the prevalence of scabies and its complications. Out of 170 children interviewed 100 were found infected by scabies, 55 (55.55%) cases were male and 45 (44.44%) cases were female children. Factors like occupation of the parents, sharing of bed, congested living rooms and big family size were observed to be associated with higher occurrence of scabies.Bangladesh J. Zool. 38(1): 7-11, 2010